The impact of digital technologies on skills-to-Job mismatches - Santiago-Vela, Ana [Verfasser] (My University, 2026)
"A pervasive discourse calls for worker upskilling amid ongoing digital transformation. This study introduces a skills‐to‐ job mismatch perspective into research on the digital transformation of work by conceptualising technological adoption as a process that reshapes the relationship between workers’ skill endowments and evolving job requirements. To empirically address this perspective, the study combines German individual‐ and establishment‐level data with an entropy balancing method. The findings reveal that adopting new digital technologies in the workplace is associated with greater underskilling and reduced overskilling (i.e., skill underutilisation). Furthermore, effect heterogeneity emerges across the level of digitalisation in economic sectors. Technology adoption is more strongly associated with lower overskilling in less digitally mature sectors, while the positive association with underskilling is evenly distributed across sectors. Overall, this study provides a theoretically grounded framework and an informed empirical basis for a more nuanced debate on the digital transformation of work." (Author's abstract ; BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; G 2.2.1 Technologisierung; G 2.3 Wandel von Arbeit & Wirtschaft; G 2.3.4 Qualifikationswandel; 370; Arbeitsmarkt; Arbeitsplatz; Transformation; Zukunft der Arbeit; Qualifikationsanforderung; Beschäftigungsfähigkeit